Antonia Pozzi: se Dio non è lontano (Materiali di Estetica. Terza serie, 2019)
Antonia Pozzi (Milan 1912-1938) does not believe in a confessional God. According to her, God comes alive in human heart. The poet, thanks to her sensitivity and personality, had a strong spirituality. Her ascensional tension and research of sense and absolute (with all the distress that comes with it) have been aconstant ofherlife,whichculminatedinthelovefortheProf.Cervi and found expression through the love for human being and the creation of poetry.